PEMEKARAN KECAMATAN DI KABUTEN SOLOK, LAHIRNYA KECAMATAN TIGO LURAH (2001-2011) - Linda, Desra; Nazmi, Ranti; Aziz, Zulkifli (Pendidikan Sejarah, 2013)
ABSRACTThis thesisexamines theprocess of expansionTigoDistrictHeadman, whoofficiallysplit from theUmbrellaSekakiDistrictin 2001withthe release ofSolokRegency RegulationNo.5of 2001concerningthe establishment ofDistrictTigoVillage andtwootherdistrictsin Solok. Besidesalsoseehow thedevelopmentsafter the splitin the economic, education,health,andpoliticsthatisappointfourimportantareas ofpublic welfarewhichis the goal ofthe division. This research aimstoexplainthe background of theexpansionin the subdistrictheadmanTigo(2001-2011), describesthe process of expansionTigoDistrictHeadmanandimpactafterthe divisionheld.This study wasconducted usinghistoricalresearch methods, withthe followingstages: The firstheuristic, it is asourcecollectsliterature, documents, recordsandinterviews. The secondsource ofcriticism, is thetestactivitysourcesthat have beencollectedthroughinternalandexternalcriticism. The thirdinterpretation, istointerpretthe factswiththe factthatoneway of connectingwithotherfactsin accordancewith thehistorical eventsthatincludes the time, place, andevents, the fourthhistoriography, ispresentingresearch resultsin the form ofthesis.The results showed that, first a desire to split the district in Solok regency and form the District Headman Tigo as the definitive districts due to lack of government attention to this area . State of the separated region because there is no adequate transportation access make this isolated area, so it appears the economy, education , health and pilitik . Tigo District Headman two officially bloomed in 2001 . Third , after the subdistrict headman bloomed Tigo , which has lasted for a decade that has not received attention from the government entirely is still being isolated districts in Solok regency . It can be concluded , first the peoples desire to split the area in Solok District and forming Tigo Headman, second, the establishment of a decade Tigo District Headman not show changes to the surrounding communities, who live with the limitations paced.Â Keywords: regional growth, power, rule